KEANEKARAGAMAN JENIS BURUNG DI KAWASAN HUTAN DESA, DESA LONCA KECAMATAN KULAWI KABUPATEN SIGI - Wibowo, Yuda; Labiro, Elhayat; Sustri, Sustri (Universitas Tadulako, 2017)
Birds are the fauna with extensive range of habibat, from lowlands to highlands, as well as various types of ecosystems, from natural to artificial ecosystems. In addition to their significant role in the the ecosystem balance, birds serve as an indicator of environmental changes. The aim of this study was to determine the level of the bird presence, species composition, and species diversity in the forest located at Lonca Villages, Kulawi District, Sigi Regency, Central Sulawesi Province. Line transects method was employed in the field study where the observers walk along the direction and center-line of the transect steadily and record occurences of the entire birds. Observations were performed at 06:00-09:00 a.m. (Central Indonesian Time/Wita) and 03:30-06:00 p.m. (Central Indonesian Time/Wita). Observations were replicated 4 (four) times. Based on the results of measurement, there were 27 species of birds representing 16 families with a number of individuals of 142 birds in two different habitat types. More results showed the species composition in the study area. Index of species diversity in open habitat was H’=2,8881 and in closed habitat was H’=2,8070, t-test result of species diversity index between those habitat types was similar. Sulawesi hornbill (Rhyticeros cassidix), Black-crowned White-eye (Zosterops atrifrons), and Hair-crested Drongo (Dicrurus hottentottus) dominate the two habitat types.